(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article is devoted to the linguistic approach to teaching practical English grammar at a language university. Interest in the problem of joint learning of languages and cultures is growing every year. Presenting material without a cultural component is considered ineffective and does not contribute to the formation of a secondary linguistic personality. This problem is relevant for all levels of education, including higher education.